Education standards in the environmental ethics social development today - THỊ DIỆU HẰNGPHẠM (Tạp chí Nghiên cứu Khoa học Công đoàn, 2020)
The environment is the surrounding world that is affecting human existence and development, the environment is thebirthplace and development of human beings. However, in the present condition due to the exploitation of any Human reasoning hasled to the depletion of natural resources, polluting the ecological environment. Environmental protection has become a global issue.Therefore, the improvement of environmental ethics and the education of ethical standards in the context of modernization in ourcountry is necessary.